Intention to comply with solid waste management practices among households in Butajira town, Southern Ethiopia using the theory of planned behavior. - Semu Debebe Fikadu; Abinet Arega Sadore; Gizachew Beykaso Agafari; Feleke Doyore Agide (PLoS ONE, 2022)
Background One of the world's most serious environmental issues is solid waste management. It is critical for researchers to understand the intention to comply with solid waste management. Thus, we aim to determine the intention to comply with solid waste management practice among households in Butajira Town using the Theory of Planned Behavior. Method A community-based cross-sectional study was conducted on a sample of 422 households in Butajira from June 1 to June 30, 2020. The constructs and principles of the theory of planned behavior (TPB) were measured. We selected using a systematic sampling method and collected data by using a structured interviewer-administered questionnaire. Data was analyzed using SPSS version 25.0. The predictors of intention to practice solid waste management were identified using a multivariable linear regression model. A P-value of less than 5% was considered to declare a significant association. Results The findings demonstrated that intention to practice solid waste management explained 86% of the variance explained by all predictors. The perceived behavioral control construct had the greatest impact on households' behavioral intentions to comply with solid waste management practice (β = 0.16; CI (0.14, 0.18), followed by attitude (β = 0.15; CI (0.11, 0.21) and subjective norms (β = 0.12; CI (0.06, 0.17). Conclusion Our study also found that intention has a substantial influence on the behavior of solid waste management practices. Therefore, there is a need to enhance service utilization for solid waste management and to improve outdoor solid waste dropping behavior through door-to-door collection services by municipality. Furthermore, further longitudinal research should be done through intervention mapping.